Teacher AI Literacy in Digital Teaching Material Development: An Observational Study in Yogyakarta - Amalina Nur Arifah; Muhammad Haedar Zhafran Hidayatulloh; Muhammad Fauzan Gustafi (Journal of Creative Power and Ambition (JCPA), 2026)
The integration of Artificial Intelligence (AI) in education is increasingly urgent in the era of digital transformation, yet AI literacy levels among Indonesian educators remain insufficiently mapped. This study aims to analyse AI literacy levels among primary and secondary school teachers in the context of digital teaching material development in Yogyakarta. Using a descriptive-qualitative design with an observational approach, the study involved 161 educators across educational levels observed during four AI, AR, and VR workshop sessions in Yogyakarta. Data were collected through structured observation and field notes, and analysed using reflexive thematic analysis. Results revealed significant differences in generative AI exposure: all teachers with less than five years of teaching experience (49 teachers, 100%) had been exposed to generative AI, while 72.32% of senior teachers (81 out of 112) had comparable exposure. Thematic analysis identified three main themes: (1) varying patterns of AI exposure and technology readiness, (2) barriers to AI adoption encompassing infrastructure, mindset, and competency factors, and (3) preferences for practice-based training. These findings are interpreted through the Technology Acceptance Model (TAM) and Diffusion of Innovation frameworks, contributing to theoretical understanding of intergenerational gaps in educational technology adoption in Indonesia.